A clinical study on obstructed inguinal hernia: a descriptive study on 53 cases - Padmasree, Gaddam (International Surgery Journal, 2019)
Background: Inguinal hernias are the common causes of surgical admissions and referral of patients from primary physicians. Although we have made a great progress in treating hernia the management of its complications has progressed only a little. The aim of study was to determine the various modes of presentation, clinical features, diagnostic and therapeutic strategies and to evaluate the post-operative outcome in obstructed hernia surgeries. Methods: After obtaining written and informed consent from the patients, cases for the study were randomly selected from patients admitted to this tertiary care hospital for surgical intervention of inguinal hernias during the period between 2015 and 2017. Cases with inguinal hernias which had signs of obstruction and inability to reduce the hernia are taken up for emergency surgical intervention within 6-8 hours. Results: 53 obstructed inguinal hernia patients were evaluated and found that, incarceration was the commonest complication seen in 92.45% of cases followed by strangulation (7.54%). Viable bowel was seen 88.67% of cases. Bowel resection and end-to-end anastomosis was done in all cases of non-viable bowel. The commonest post-operative complication encountered in the study was wound infection (9.43%) and scrotal seroma (9.43%). Conclusions: The most common content was small bowel followed by omentum (52.8% and 35.8% respectively). Wound infection and seroma were the most common complications (9.43%) and mortality was observed in two patients (3.7%) and the causes of death were sepsis and acute respiratory distress syndrome.